2018
DOI: 10.21776/ub.ijhn.2018.005.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Penyuluhan Gizi untuk Mengubah Pengetahuan dan Sikap Masyarakat terhadap Pengembangan Pangan Lokal Salak Manonjaya

Abstract: Salak Manonjaya merupakan salah satu varietas asli Indonesia yang saat ini pamornya semakin menurun akibat memiliki kualitas rasa kurang disukai dibandingkan dengan salak yang ada di pasaran. Varietas ini di masa yang akan datang dikhawatirkan hilang, sehingga diperlukan upaya revitalisasi pemanfaatan salak ini yaitu dengan diversifikasi produk olahan serta didukung dengan upaya sosialisasinya. Tujuan penelitian ini adalah melihat perubahan pengetahuan dan sikap masyarakat dalam memahami dan mendukung upaya pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…One of the counseling media used in this community service is using tempe product demos made from non-soybeans and yogurt from local nuts and Manonjaya salak. Even though the target groups are different, the media used is almost the same as the research conducted on 90 SD/MI students through counseling with a simulation of selecting food sources of nutrients with pictures in Depok City (Sartika, 2011) and Manonjaya salak processed products for junior high school students in the District Manonjaya, Tasikmalaya Regency (Bachtiar et al, 2018). In addition, this method is also carried out in increasing the capacity of disaster emergency food organizers (Sumarto, et al, 2019).…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the counseling media used in this community service is using tempe product demos made from non-soybeans and yogurt from local nuts and Manonjaya salak. Even though the target groups are different, the media used is almost the same as the research conducted on 90 SD/MI students through counseling with a simulation of selecting food sources of nutrients with pictures in Depok City (Sartika, 2011) and Manonjaya salak processed products for junior high school students in the District Manonjaya, Tasikmalaya Regency (Bachtiar et al, 2018). In addition, this method is also carried out in increasing the capacity of disaster emergency food organizers (Sumarto, et al, 2019).…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…One food ingredient that has high fiber has the potential to be added to sinbiotic food, namely Manonjaya salak. Based on the results of the study, it showed that the fiber and carbohydrate content in Manonjaya salak flour was quite high (Bachtiar et al, 2018;Aprianty et al, 2018). Fiber acts as a prebiotic that supports the growth of probiotics in the gut (Kusharto, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…dan penyuluhan tentang pengembangan pangan lokal salak Manonjaya(Bachtiar et al, 2018). Metode demonstrasi dalam Pendidikan gizi yang dapat meningkatkan keterampilan sasaran…”
unclassified